Entrepreneurship Textbook Development in Implementing UNJA's Vision to Support UNJA Civics Study Students’ Creativity Programs - Heri Usmanto; Dona Sariani; Irwan Irwan (International Journal Labs, 2021)
Textbooks can make students understand what their teacher is conveying. A good and understandable textbook will make it easier for students to comprehend what they are supposed to learn. However, at the University of Jambi, especially in the Civics Study Program, there are no entrepreneurship teaching materials supporting student learning activities in the classroom. Therefore, this research aims to discover the aspects of entrepreneurship course textbooks that need to be developed in improving hard skills as technical abilities and soft skills to support the hard skills. The results of this research only scope the validation test stage, namely the validation of material experts and media validation and language validation. Wherefrom the results of the validator show the feasibility of the textbook that was developed to be tested and implemented to students during the learning process in the Civics Study Program, University of Jambi.